2019
DOI: 10.1126/sciadv.aau8301
|View full text |Cite
|
Sign up to set email alerts
|

Accessing neuroinflammation sites: Monocyte/neutrophil-mediated drug delivery for cerebral ischemia

Abstract: Cerebral ischemia (CI) results from inadequate blood flow to the brain. The difficulty of delivering therapeutic molecules to lesions resulting from CI hinders the effective treatment of this disease. The inflammatory response following CI offers a unique opportunity for drug delivery to the ischemic brain and targeted cells because of the recruitment of leukocytes to the stroke core and penumbra. In the present study, neutrophils and monocytes were explored as cell carriers after selectively carrying cRGD lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 42 publications
(48 reference statements)
0
56
0
Order By: Relevance
“…Recently, new assessments have been applied in clinical studies to improve the outcomes of ischemic stroke. Hou et al reported the results of a new trial that showed that using monocytes and neutrophils, which were developed as carriers for cRGD [cyclo (Arg-Gly-Asp-D-Tyr-Lys)] liposomemediated drug delivery, may alleviate ischemic stroke outcomes (177). Targeting monocyte that protects neuronal cell death through nanotechnology could be a novel therapeutic strategy for ischemic stroke.…”
Section: Applied Nanotechnologiesmentioning
confidence: 99%
“…Recently, new assessments have been applied in clinical studies to improve the outcomes of ischemic stroke. Hou et al reported the results of a new trial that showed that using monocytes and neutrophils, which were developed as carriers for cRGD [cyclo (Arg-Gly-Asp-D-Tyr-Lys)] liposomemediated drug delivery, may alleviate ischemic stroke outcomes (177). Targeting monocyte that protects neuronal cell death through nanotechnology could be a novel therapeutic strategy for ischemic stroke.…”
Section: Applied Nanotechnologiesmentioning
confidence: 99%
“…Many acute and chronic inflammatory disorders in the brain involve inflammation of both the parenchyma and the vasculatures. Lastly, we sum up present BBB leakages of current studies in the condition of stroke [ 179 ], cerebral ischemia [ 180 ], sepsis [ 181 , 182 ], Malaria [ 183 , 184 ], intracellular parasite [ 185 ], SARS-CoV-2 [ 177 , 178 ], MS [ 186 ], systemic lupus erythematosus (SLE) [ 187 ], and even AD [ 188 ] and EAE [ 89 ]. Other viral infections and parasite invasion would increase the risk [ 189 , 190 , 191 ].…”
Section: Main Textmentioning
confidence: 99%
“…[ 8 ] Another study designed nanocarriers to attach to neutrophils and monocytes in circulation that subsequently delivered the cargo to ischemic brain tissue. [ 14 ] This demonstrates that neutrophils can be used as carrier cells for drug delivery. [ 15 ] Due to the involvement of inflammation and neutrophils in many diseases, loading neutrophils with drugs or drug‐loaded nanocarriers ex vivo and reinjecting these hybrids into the patient has the potential of becoming a vital tool to deliver drugs locally to remote inflammatory sites despite systemic administration to dampen uncontrolled inflammation.…”
Section: Figurementioning
confidence: 99%